The vegetation–topography heterogeneity coupling in the Loess Plateau, China - Luo, Zhihui; Liu, Yu; Zhou, Hongyi (Frontiers in Environmental Science, 2024)
As a result of adaptation to environment, the great environmental spatial heterogeneity leads to the high spatial heterogeneity of vegetation status. This coupling maybe more apparent in the water-limited drylands, where the topography is the main determinant of small-scale variation of water availability and energy. Metric describing this coupling may contribute to detection of the extension of vegetation reshaping by human intervention and other driven forces. In this study the Heterogeneity Index of Coupling (HIC)was developed to indicate the coupling between spatial heterogeneity of vegetation status (Hv) and the spatial heterogeneity of topography (HT) in the Loess Plateau in northern China. The 16-day composed MODIS normalized vegetation index (NDVI) with a resolution of 250 m and SRTM DEM were employed to quantify the heterogeneity of vegetation status and the topographical heterogeneity. The results show that HIC varies among geomorphic zones, land cover types and land cover change categories. Among all land cover types, HIC of sandy area was the largest, followed by HIC of forest, shrub, farmland land and grassland. Among geomorphic zones, the highest of HIC value appeared in plains with dense residential area , followed by sandy land that frequently reshaped by wind, rocky mountainous areas, hilly and gully loess plateau, and loess tableland. It was revealed that the alternation of vegetation by human activities and natural disturbance shaped greater HIC. Results of this study approved the effectiveness of the HIC in reflecting the coupling of vegetation status with topography.